Indigenous Life Courses, Racialized Gendered Life Scripts, and Cultural Identities of Resistance and Resilience - Alook, Angele (2016)
The aim of this research project was to understand the cultural identity of young Indigenous adults living between on-reserve, off-reserve rural settings, and the city. The secondary research question examined the gendered experiences of family, school, and work in this process. I interviewed men and women, 16 from the city of Edmonton, and 15 living in Wabasca, Alberta. This study uses my brand of Indigenous Sociology, in which I combine Cree Indigenous research methodologies, Indigenous feminism, and a life course approach. As background, I lay out the complex geographic, demographic, historical and colonial context of the migration experiences, and show that Indigenous peoples continue to live under a colonial regime that geographically and racially divides us. Findings from interviews reveal cultural identity is based on family relations. Key themes explored are: the child as central to family and community; family as central to building healthy relations and cultural identity; and positive and negative understandings of community. I explore a theory on bouncing among family relations and locations, while balancing family, school and work. One of the key findings of this study is how extended family networks provide for moral support, financial support, and childcare support for those that choose to complete an education and become steadily employed. I present Indigenous models of family as a form of resistance and resilience to colonialism, and that healthy family relations are built in different locations. I present the interview findings on school and work choices. I outline the colonial structures of education which impact access to schooling and funding, which are divided along geographic and racial lines. I examine specific factors that acted as barriers and facilitators to achievements in school and work. I finish by explaining that community members must contend with racialized gendered life scripts along their life courses. Specifically, Indigenous women must contend with life scripts that expect a ...